The Unfortunate Regressivity of Public Natural Hazard Insurance: A Quantitative Analysis of a New Zealand Case - Sally Owen; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2017)
Natural hazard insurance is almost always provided through public-private partnerships. Given the dominant role of the public sector, it is surprising that equity issues have not faced more scrutiny with respect to the design of hazard insurance. We provide a detailed quantification of the degree of regressivity of the New Zealand earthquake insurance program – a system that was designed with an egalitarian purpose. We measure this regressivity as it manifested in the half a million insurance claims that resulted from the Canterbury earthquakes of 2011. As in other cases, this can be remedied with modifications to the program's structure.
Keywords: D30; 330; insurance; redistribution; regressivity; tax